Hierarchical Porous Carbon Nitride-Crumpled Nanosheet-Embedded Copper Single Atoms: An Efficient Catalyst for Carbon Monoxide Oxidation - Eid, Kamel; Sliem, Mostafa H; Al-Ejji, Maryam; Abdullah, Aboubakr M; Harfouche, Messaoud; Varma, Rajender S (ACS applied materials & interfaces, 2022)
Rational design of metal single-site embedded porous graphitic carbon nitride (P-g-C3N4) nanostructures exploiting maximum atom utilization is warranted to enhance the thermal CO oxidation (COOx) reaction. Herein, a facile, green, one-pot, and template-free approach is developed to fabricate the hierarchical porous P-g-C3N4-crumpled ultrathin nanosheets atomically doped with copper single atoms (Cu-P-g-C3N4). Mechanistically, the quick protonation of melamine and pyridine under acidic conditions induces deamination to form melem, which is polycondensed under heating. The interconnected pores, high surface area (240 m2g-1), and maximized exposed isolated Cu atomic active sites (1.8 wt %) coordinated with nitrogen atom P-g-C3N4 are the salient features of Cu- P-g-C3N4 that endowed complete conversion to CO2 at 184 °C. In contrast, P-g-C3N4 only converted 3.8% of CO even at 350 °C, implying the electronic effect of Cu single atoms. The abundant Cu-nitrogen moieties can drastically weaken the binding affinity of the CO-oxidation (COOx) intermediates and products, thus accelerating the reaction kinetics at a low temperature. This study may promote the fabrication of P-g-C3N4 doped with various single atoms for the oxidation of CO.
Keywords: CO oxidation reaction mechanism; porous g-C3N4; Cu single site; carbon nitride; CO oxidation